Associations of objectively assessed physical activity and sedentary time with health-related quality of life among lung cancer survivors: A quantile regression approach - D'Silva, A.; Gardiner, P.; Boyle, Terry; Bebb, D.; Johnson, S.; Vallance, J. (Elsevier, 2018)
Objectives: No studies have examined objectively assessed physical activity, sedentary time, and patient-reported outcomes among lung cancer survivors. The objective of this study was to determine associations of objectively assessed moderate-to-vigorous intensity physical activity (MVPA) and sedentary time with health-related quality of life (HRQoL) and fatigue among lung cancer survivors. Materials and method: Lung cancer survivors in Southern Alberta (N = 540) were invited to complete a mailed survey that assessed HRQoL [Functional Assessment of Cancer Therapy-Lung (FACT-L)], physical and functional well-being [Trial Outcome Index (TOI)] , and fatigue [Fatigue Scale (FS)]. Physical activity and sedentary time data was collected using an Actigraph ® GT3X+ accelerometer that was worn on the hip for seven consecutive days. Quantile regression was used to examine associations of HRQoL and fatigue with physical activity and sedentary time at the 25th, 50th, and 75th HRQoL and fatigue percentiles. Results: A total of 127 lung cancer survivors participated for a 24% response rate (Mean age = 71 years; Mean time since diagnosis = 75 months). Total MVPA minutes was positively associated with fewer fatigue symptoms at the 25th percentile (β = 0.16, p = 0.046). Total sedentary time was inversely associated with HRQoL at the 75th percentile (β = −0.07, p = 0.014) and inversely associated with fatigue symptoms at the 50th percentile (β = −0.04, p = 0.009). Total sedentary time was also inversely associated with physical and functional well-being scores at the 25th (β = −0.07, p = 0.045), 50th (β = −0.07, p = 0.004) and 75th (β = −0.04, p = 0.035) percentiles. Conclusion: Across the HRQoL, fatigue, and physical and functional well-being distributions, sedentary time was inversely associated with HRQoL, fatigue, and physical and functional well-being in lung cancer survivors. Small associations were observed between MVPA and fatigue, but no associations emerged with HRQoL or physical and functional well-being.